The Importance of Visum Et Repertum in the Crime of Serious Theft - Vincentius Patria Setyawan (ARIMA : Jurnal Sosial Dan Humaniora, 2023)
The problem discussed in writing this article is the legal consideration of the panel of judges regarding post mortem et repertum in criminal acts of theft with violence that causes death. This problem was analyzed using normative legal research methods with a case approach to Decision Number: 208/Pid.B/2022/PN.Bdg. The technique for collecting legal materials in writing this article uses literature study of primary legal materials and secondary legal materials. The results of this research are that the importance of the existence of a post mortem et repertum is that law enforcement officers, especially judges, are not equipped with knowledge of forensic medicine, so in seeking material truth judges need to consider expert information contained in the visum et repertum. Apart from that, the post mortem et repertum in Decision Number: 208/Pid.B/2022/PN.Bdg is worthy of consideration in evidence because it is in accordance with the statements of the witnesses prese